AN ERA OF CHANGING THE ENVIRONMENTAL CONDITION BY GREEN SUPPLY CHAIN MANAGEMENT - Singh, Pratiksha; Singh, Naman; Kumar, Gaurav; Kumar, Virendra; Dwivedi, Swati; Dixit, Shubhangi; Pandey, Srinath; Mishra, Ved Kumar; Jain, Prashant Ankur (International Journal of Research -GRANTHAALAYAH, 2017)
Green supply chain management is defined as the process of using environmentally friendly inputs and transforming these inputs into outputs that can be reclaimed and re-used at the end of their life cycle thus, creating a sustainable supply chain. GSCM is one of the recent innovations for the enhancement of capabilities of Supply Chain Management. The purpose of this paper is to carry out a theoretical review of Green supply chain management (GSCM). The assessment involved 144 research articles published in 48 selected journals between 1998 and 2013. The methodology of empirical research involved selection and classification of 144 research articles in GSCM. A systematic classification and a critical analysis is carried out so as to identify research gaps in content of GSCM, as well as to recommend directions for future research. It is concluded from the analysis of the results that research in GSCM is increasing at a faster rate than ever; with theory building more in focus than verification. Furthermore, a new taxonomy was proposed on the basis of content and research methodology utilised. Based on this taxonomy, significant trends were observed and some unique inferences were drawn, apart from identifying the directions for future research. There have been a couple of literature reviews in GSCM but none of them focused exclusively on research methodology in GSCM. Also the sample size with respect to the number of papers (144 papers), as well as number of journals (48 journals), is larger than ever considered for literature review in GSCM. The papers spans a longer time period of 16 years (1998-2013).